Empathy Development in Early Grade at State Elementary Schools - Muh Shaleh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to measure and inform the level of empathy (affective and cognitive) of early grade students aged 6-8 years at SDN Baruga Kendari, Southeast Sulawesi. Seven schools were selected as the sample based on a methodology called Random Sampling. The sample in this study were children aged 6-8 years, totaling 150 students. The research method used in this research is quantitative research. The data collection technique is to use a questionnaire applied to collect data about the development of children's empathy. The questionnaire refers to children's empathy using the GEM (Griffith Empathy Measure) scale, which is designed to assess a child's level of empathy for the conditions they are experiencing. Criteria scores for each statement were